Oligomer formation of SARS-CoV-2 ORF8 through 73YIDI76 motifs regulates immune response and non-infusion antiviral interactions - Assadizadeh, Mohammad; Azimzadeh Irani, Maryam (Frontiers in Molecular Biosciences, 2023)
Open Reading Frame 8 (ORF8) is a 121 amino acid length SARS-CoV-2 specific accessory protein that plays crucial roles in viral infectivity, and pathogenesis. Current SARS-CoV-2 treatments focus on spike or RNA-dependent RNA polymerase proteins. Hence, directing attention to ORF8 yields substantial benefits for innovative non-infusional therapeutics. Functional ORF8 is proposed to form oligomers via a crystallographic contact centered by 73YIDI76 motifs. Hence, the structure and atomistic interactions of trimeric and tetrameric ORF8 oligomeric forms were modeled by means of thorough molecular modeling and molecular dynamics simulations. Results show that trimeric and tetrameric oligomers are stabilized by the interaction of β4-β5(47-83) loops. 73YIDI76 motifs are involved in obtaining the oligomerization interfaces. It is shown that the tetramers which resemble a doughnut-like construction are the most stabilized oligomeric forms. Where four β4-β5 loops form the interfaces between two dimers. Each monomer links to two others through β4-β5 loops and a covalent Cys20-Cys20 bridge. Epitope mapping, binding site predictions, and SASA analyses of different ORF8 forms show that the B-cell, MHC-I, and drug epitopes stay exposed in oligomeric forms. Approving that the viral infectivity is expanded upon ORF8 oligomerization and the regions involved in oligomerization can be considered as therapeutic targets.